2019
DOI: 10.1080/16078454.2019.1660458
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of early death in adult patients with secondary hemophagocytic lymphohistiocytosis: a single-institution study of 171 Chinese patients

Abstract: Xie (2019) Risk factors of early death in adult patients with secondary hemophagocytic lymphohistiocytosis: a single-institution study of 171 Chinese patients, Hematology, 24:1, 606-612, ABSTRACT Background: Adult secondary hemophagocytic lymphohistiocytosis (HLH) is a potentially lifethreatening syndrome characterized by excessive activation of mononuclear-phagocytic system resulting in hyperinflammatory response. To date, the factors influencing early death of HLH are still not fully elucidated. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
7
35
3
Order By: Relevance
“…In our study, no statistically significant differences were observed between the different subgroups (24). This may be due to the fact that the AI subgroup presented lower mortality and a greater liver alteration.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In our study, no statistically significant differences were observed between the different subgroups (24). This may be due to the fact that the AI subgroup presented lower mortality and a greater liver alteration.…”
Section: Discussioncontrasting
confidence: 74%
“…In general, the malignant neoplasms underlying HPS, especially lymphoma, are considered an adverse prognostic factor. (10,11,24,27).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, thrombocytopenia results in an increased risk of bleeding, impaired immune response, and bone marrow failure, suggesting a worse prognosis. were no differences between the etiological subgroups or by survival group, unlike other studies, where hypertriglyceridemia proved to be a predictor of adverse outcome [14]. This may be because most of our patients in the survival group were patients with AI disease, who had lower mortality and greater liver alteration.…”
Section: Discussioncontrasting
confidence: 62%
“…LDH was often regarded as an indicator of organ injury and tumor burden. 18 Previous studies found that high level LDH were common in severe cases and correlated with severe acute lung injury. 12,16 The present study revealed that high level LDH was associated with prolongation of viral shedding time, which may be due to the severe lung injury.…”
Section: Discussionmentioning
confidence: 99%